1998
DOI: 10.1007/978-94-011-4786-6_11
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant insulin-like growth factor-I (IGF-I) production in Super-CHO results in the expression of IGF-I receptor and IGF binding protein 3

Abstract: Previously, we described the genetic construction Super-CHO, a cell line capable of autocrine growth under fully defined protein-free conditions. Super-CHO cells constitutively express insulin growth factor-I (IGF-I) and transferrin in sufficient amounts to support long-term, stable growth without the addition of exogenous growth factors, thus making it an ideal host for the production of recombinant biopharmaceuticals. although IGF-I has been successfully expressed in Chinese Hamster Ovary (CHO) cells, the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
(17 reference statements)
0
6
1
Order By: Relevance
“…Specific growth rate, µ (h -1 ) mean ± SD Doubling time, tD (h) mean ± SD 87 x 10 4 ± 9.098 0.058 ± 0.020 11.000 ± 3.416 The different thickness of the bands may be related to the growth stage where the samples were taken and this warrants further investigation. In contrast to a study by Sunstrom (1998), we success-fully showed that CHO-KI natively expressed the IGF-1 gene. This information is vital for future recombinant strategies to engineer efficient mammalian cell culture system, in particular targeting at IGF-1 axis.…”
Section: Time (H)contrasting
confidence: 92%
See 1 more Smart Citation
“…Specific growth rate, µ (h -1 ) mean ± SD Doubling time, tD (h) mean ± SD 87 x 10 4 ± 9.098 0.058 ± 0.020 11.000 ± 3.416 The different thickness of the bands may be related to the growth stage where the samples were taken and this warrants further investigation. In contrast to a study by Sunstrom (1998), we success-fully showed that CHO-KI natively expressed the IGF-1 gene. This information is vital for future recombinant strategies to engineer efficient mammalian cell culture system, in particular targeting at IGF-1 axis.…”
Section: Time (H)contrasting
confidence: 92%
“…Baserga (1993) reported that recombinant CHO cells constitutively expressing IGF-1 (and IGF-1R) were able to grow in serum free media without the addition of exogenous growth factor which would in part reduce cost. Meanwhile, Sunstrom et al (1998) described the ability of Super-CHO cells to constitutively express IGF-1 and transferrin in sufficient amounts to support long-term, stable growth without the addition of exogenous growth factors, thus making it an ideal host for the production of recombinant biopharmaceutical. Although, previous in vitro investigations have demonstrated expression of IGF-1 in cell lines derived from mesenchymal and epithelial tissues as well as cancers (Sekyi-Otu et al, 1995), IGF-1 gene has been reported not to be normally expresssed in CHO cells while IGF-1R has been reported to be below the detection limit (Sunstrom et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Proteins in the clear supernatant were separated on a 4-20% Tris glycine polyacrylamide gel and repressor protein was detected using a rabbit anti-lac repressor polyclonal sera (Stratagene) followed by an alkaline phosphataseconjugated anti-rabbit IgG. IGF-I was detected in the conditioned medium using an enhanced chemiluminescent (ECL) dot blot method (Sunstrom et al, 1998). Protein concentration of hGH in the conditioned medium was determined using reverse phase high performance liquid chromatography (HPLC) using a Hamilton PRP-∞ column (Hamilton, cat no 79470).…”
Section: Methodsmentioning
confidence: 99%
“…A number of authors have suggested that IGF-I could substitute for insulin in cell culture medium, either by exogenous addition (Rasmussen et al 1998), or by engineering the cell lines to produce their own IGF-I (Hunt et al 1997;Li et al 2000;Sunstrom et al 1998;Sunstrom et al 2000). However, exogenous addition of IGF-I is complicated by the presence of IGF binding proteins (IGFBP) secreted by the cells.…”
Section: Use Of Insulin and Insulin-like Growth Factors (Igf) In Cellmentioning
confidence: 99%
“…However, exogenous addition of IGF-I is complicated by the presence of IGF binding proteins (IGFBP) secreted by the cells. In vivo, virtually all of the secreted IGF-I appears to be bound by one of at least six IGFBPs which have significantly higher affinity for IGF-I than the IGF receptors (Holly 2004), and in one of the CHO cell studies in which IGF-I was exogenously expressed, IGFBP-3 expression was induced in response to the presence of IGF-I, potentially limiting the effectiveness of IGF-I at stimulating growth (Sunstrom et al 1998). To alleviate the effects of IGFBPs, an IGF-I analog (LONG Ò R 3 IGF-I) was developed by Novozymes (previously Gropep) in which the third amino acid, glutamate was replaced by arginine (Francis et al 1992), reducing the affinity of LONG Ò R 3 IGF-I for IGFBPs by [ 100-fold without compromising its biological potency.…”
Section: Use Of Insulin and Insulin-like Growth Factors (Igf) In Cellmentioning
confidence: 99%